Log in to add a comment

## Answers

The given expression becomes

3p² -2(p + 5) - 6

= 3p² - 2p - 16

= 3p² + 6p - 8p - 16

= 3p(p + 2) - 8(p + 2)

= (p + 2)(3p - 8)

Now put replace with x² - 5x, above becomes

= (x² - 5x + 2)((3x² - 15x - 8)

**Since, x²- 5x is equal in both the cases**

**So, x²- 5x =a**

**Placing a,**

**3a² -2(a + 5) - 6**

**= 3a² - 2a - 16**

**= 3a² + 6a - 8a - 16**

**= 3a(a + 2) - 8(a + 2)**

**= (a+ 2)(3a - 8)**

**Now replacing the value of a,we get**

**(x² - 5x + 2)(3x² - 15x - 8)**